Food preparation and cookery : an international approach. - Finch, Clive F. (Longman, 1998)
This book presents approachs for food preparation and cookery as: Appetisers; Soups; Egg and Cheese Dished; Farinaceous Dishes and Dumplings; Pizzas, Rice and Grain; Fish; Meats; Poultry; Game; Vegetable and Potato Dishes; Sweets and Bakery Items; and Stocks and Sauces...